Calreticulin regulated intrinsic apoptosis through mitochondria-dependent and independent pathways mediated by ER stress in arsenite exposed HT-22 cells. (July 2020) - Wang, Xiaotong; Liu, Xudan; Chen, Yao; Wang, Huanhuan; Zhang, Ruo; Zhang, Qianhui; Wei, Yuting; Shi, Sainan; Li, Xin
Abstract: Arsenic is a naturally occurring environmental toxicant. Chronic exposure to arsenic is linked with neurological damage. Although the mechanisms remain to be elucidated, it is currently believed that neural cell apoptosis is one of the underlying mechanisms of arsenic-induced neurotoxicity. Calreticulin (CRT) is a quality control chaperone located in the lumen of the endoplasmic reticulum (ER), which participates in many signaling pathways including apoptosis. However, the role of CRT in apoptosis is controversial. Whether CRT plays a role in arsenite-induced apoptosis and the relationship between CRT and ER stress-mediated apoptosis have not been mentioned before. In this study, we found that CRT expression as well as the cell apoptosis levels increased in a dose dependent manner upon arsenite exposure in HT-22 cells, a mouse hippocampal neural cell line. In addition, arsenite exposure resulted in the up-regulation of ER stress indicator GRP78 and ER stress-related proteins including p -PERK, ATF4, CHOP, calpain2 and cleaved caspases-12, accompanied by the down-regulation of Bcl-2 and up-regulation of Bax and cleaved caspase-3. Silence of CRT remarkably alleviated arsenite-induced apoptosis and reversed the expression of the proteins above. Our findings confirmed the role of CRT in the induction of apoptosis upon arsenite exposure and suggested that CRT mediated the intrinsic apoptotic cell death including both mitochondria-dependent (PERK/ATF4/CHOP/Bcl-2) and independent (calpain2/caspases-12) pathways initiated by ER stress, which we believed to be a previously undocumented property of arsenite-induced apoptosis. Highlights: CRT played a role in the induction of apoptosis upon arsenite exposure. CRT regulated mitochondria-dependent apoptosis through PERK/ATF4/CHOP. CRT regulated mitochondria-independent apoptosis through calpain2/caspases-12.